2018
DOI: 10.1093/heapro/day080
|View full text |Cite
|
Sign up to set email alerts
|

A disruptive cue improves handwashing in school children in Zambia

Abstract: Behavioral economics hold great promise in changing patterns of behavior that influence human health. Handwashing with soap is one such behavior that is important in reducing exposure to pathogens, and in school-age children, handwashing helps reduce absenteeism through the prevention of respiratory and diarrheal diseases. However, the gap between knowledge on the importance of handwashing and actual handwashing practice, especially with soap, persists. Many traditional behavior change communication approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…As a reminder the studies were assessed with five stars, where four stars were allocated based on the percentage of assessment criteria met, and one star was added to studies that used a randomized controlled trial methodology. Of the 29 studies included, 2 studies received one star [36,44], 21 received three stars, 2 received four stars [6,43], and 4 received two stars [25,27,32,33].…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…As a reminder the studies were assessed with five stars, where four stars were allocated based on the percentage of assessment criteria met, and one star was added to studies that used a randomized controlled trial methodology. Of the 29 studies included, 2 studies received one star [36,44], 21 received three stars, 2 received four stars [6,43], and 4 received two stars [25,27,32,33].…”
Section: Methodological Qualitymentioning
confidence: 99%
“…None of the interventions involved comparison of outcomes, regulation, self-belief, or covert learning. The interventions included as few as one BCT cluster [43][44][45] and as many as nine [34,42]. Of the 29 included studies, 3 used a single BCT cluster, 15 included 2 to 4, and 11 included 5 or more.…”
Section: Behavior Change Technique Clusters and The Com-b Modelmentioning
confidence: 99%
“…This was reinforced by sharing children's stool test results with their own parents after explaining transmission routes. Nudges to encourage handwashing with soap have been successfully applied in two previous trials but have not been examined with respect to their effect on STH infection [27,28].…”
Section: Intervention and Study Designmentioning
confidence: 99%
“…41 In Zambian public schools, a simple toilet pass fashioned out of soap attached to a rope was a strong enough contextual cue to motivate student HWWS. 42 Finally, the HiFive program may have had a sound conceptual basis but was less effective at improving rates of HWWS because of limitations in the implementation design. Specifically, teachers reported that they felt insufficiently trained to deliver all of the activities in the HiFive curriculum.…”
Section: Discussionmentioning
confidence: 99%